2022
DOI: 10.3390/nano12234284
|View full text |Cite
|
Sign up to set email alerts
|

The Rainbow Arching over the Fluorescent Thienoviologen Mesophases

Abstract: Thermofluorochromic materials exhibit tunable fluorescence emission on heating or cooling. They are highly desirable for applications ranging from temperature sensing to high-security anti-counterfeiting. Luminescent matrices based on liquid crystals are very promising, particularly those based on liquid crystals with intrinsic fluorescence. However, only a few examples have been reported, suggesting ample margins for development in the field, due to the wide range of fluorophores and supramolecular organizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Woodward et al synthesized and characterized viologens containing thiazolo [5,4-d]-thiazole as a bridging group and found that the obtained material showed an emission of light with a wavelength corresponding to the blue color and a reversible color change from yellow to dark blue as a result of the electroreduction [20]. The thienoviologens showed thermofluorochromism, which involves the switching of the emitted light from red to green and from white to blue as a result of the temperature-induced variation in the supramolecular interactions in the self-assembled phases [21]. Described by Veltri et al, N-aryl-substituted viologens based on bis(4-alkylphenyl)bipyridinium cations were found to exhibit liquid-crystalline properties and colorless-to-green electrochromism [22].…”
Section: Introductionmentioning
confidence: 99%
“…Woodward et al synthesized and characterized viologens containing thiazolo [5,4-d]-thiazole as a bridging group and found that the obtained material showed an emission of light with a wavelength corresponding to the blue color and a reversible color change from yellow to dark blue as a result of the electroreduction [20]. The thienoviologens showed thermofluorochromism, which involves the switching of the emitted light from red to green and from white to blue as a result of the temperature-induced variation in the supramolecular interactions in the self-assembled phases [21]. Described by Veltri et al, N-aryl-substituted viologens based on bis(4-alkylphenyl)bipyridinium cations were found to exhibit liquid-crystalline properties and colorless-to-green electrochromism [22].…”
Section: Introductionmentioning
confidence: 99%